1986
DOI: 10.1016/s0166-9834(00)82643-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity of titania-supported oxides. Part 1: vanadium oxide on titania in the sub- and super-monolayer regions

Abstract: P-25, 55 i3 m2gsy; 2-1 Vanadium oxid has been deposited gn TiO (washed anatase, 10 m g ; Degussa Eurotitania, 46 m g-l) gy aqueous impregnation of (NH) [VO(C 0) ] and by reaction with VOCl org&Pc sol3eEttP. VO(OR) (R=lBu) and VO(acac) in Single applications of tl?;! last taree reagents form no z more than a mon!layer of vanadium oxide VO,, a monolayer being defined as 0.10 wt.% V,O$ per m of surface. When less than about four monolayers of VD are pre ent, there is in most cases only a single TPR peak: T,,, val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
61
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(76 citation statements)
references
References 14 publications
15
61
0
Order By: Relevance
“…. Similarly, Baiker et al [21] also reported that titania supported vanadium oxide catalysts exhibited only one reduction peak as also reported by Bond et al [22] who found VO x monolayer species to be reduced in a single step from V 5? to V 3?…”
Section: Resultssupporting
confidence: 52%
“…. Similarly, Baiker et al [21] also reported that titania supported vanadium oxide catalysts exhibited only one reduction peak as also reported by Bond et al [22] who found VO x monolayer species to be reduced in a single step from V 5? to V 3?…”
Section: Resultssupporting
confidence: 52%
“…Bond et al [37,38] have demonstrated that, as the V loading increases, the formation of the polyvanadate monolayer is followed by the building of a disordered VO x phase in the one-to-four monolayers equivalent range, and (Table 5 and Figure 7), we observe indeed that V/Ti increases linearly up to 0.2 for V 2 O 5 /TiO 2 below 3.5 wt% , after which value the slope is far smaller.…”
Section: Vo X /Tio 2 /Stainless Steel Plates (Vt/ssht)supporting
confidence: 65%
“…It was found that vanadia on a titania surface forms different types of structures depending on the vanadia content and the preparation technique [27][28][29][30][31][32][33][34]. At vanadia content below 10 % of monolayer (ML), only a monomeric isolated structure exists, which has a tetrahedral coordination (VO 4 ) in dehydrated conditions [29,33].…”
Section: Introductionmentioning
confidence: 99%